Drivers and barriers to acceptance of human-papillomavirus vaccination among young women: a qualitative and quantitative study - Mortensen Gitte (BMC, 2010)
Abstract Background Human papillomavirus (HPV) is a necessary cause of cervical dysplasia and cancer, and of genital warts. Few studies have examined attitudes to HPV vaccination since the introduction of HPV vaccines. We aimed to investigate the reasons for young women's acceptance or rejection of the quadrivalent HPV vaccine after its general availability in Denmark. Method A literature review assessed attitudes towards HPV vaccination and the information was used to identify relevant questions for telephone and focus group interviews with women aged 16-26 who had decided to receive or reject HPV vaccination. 435 women across Denmark were interviewed by telephone. Qualitative interviews were undertaken in focus groups with 33 women living in Odense who had completed the telephone survey. Four focus groups were set up according to age (16-20 and 21-26 years of age) and acceptance/rejection of the vaccine. Results Of 839 women initially contacted by telephone, 794 were included, 411 (49%) said they accepted vaccination but only 201 (24%) had actually received the vaccine and these latter were interviewed. 242 women said they refused vaccination of which 234 were interviewed. Women who were undecided were excluded from the study. Prevention of cervical cancer was the main driver for acceptance of the vaccine, followed by parental encouragement and financial support, personal experience of someone with cancer and recommendation by health-care professionals. The greatest barrier to vaccination was its cost. A lack of information about the benefits of vaccination for sexually active women was also an important barrier and the older participants in particular considered that they were too old to be vaccinated. Knowledge about HPV and its role in the development of cervical cancer and genital warts was poor. Conclusions The difference between intention to be vaccinated and starting vaccination was considerable, and a large proportion of women aged 16-26 did not wish to be vaccinated. If the most important barriers to vaccination were addressed (cost and a lack of information about vaccination benefits), it is likely that the uptake of vaccination in Denmark would increase substantially.